النخب في العالم العربي: الواقع والأدوار - كعسيس خليدة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تهدف هذه الدراسة، إلى تقديم قراءة نقدية تحليلية لواقع ودور النخب في العالم العربي، من خلال الانطلاق من الإشكالية التالية: ما هو واقع النخب العربية و خصائصها؟ و فيما تتمثل إشكالياتها الفكرية و أدوارها منذ بداية الحراك العربي؟ و لمعالجة الموضوع محل الدراسة، تم الاعتماد على المنهج التاريخي لفهم الخلفيات التاريخية لتكوين الفكر العربي وتشكل النخب في العالم العربي، بالإضافة إلى المنهج الوصفي التحليلي لتوصيف وتحليل واقع ودور النخب العربية. وقد خلصت الدراسة إلى أن النجاح في بناء مشروع نهضوي في العالم العربي مرهون بمدى اضطلاع النخب المثقفة بأدوار ريادية فاعلة، كما توصلت الدراسة إلى أن المنطقة العربية تعيش أزمة خطيرة على مستوى النخب، نتيجة انعزالها عن المجتمع ومشكلاته، مما جعل الجماهير، تفقد ثقتها في النخب المثقفة، وخصوصاً في دورها الرائد في مطالب الحرية والديمقراطية والتعددية. This study aims to provide a critical and analytical reading of the reality and role of elites in the Arab world, by starting from the following problem: What is the reality of Arab elites and their characteristics? And What are its intellectual problems and roles since the beginning of the Arab movement? In order to deal with the subject under study, the historical method, and descriptive and analytical method. The study concluded that the success in setting up a project for the renaissance in the Arab world requires that the elites play effective roles, but the Arab region is experiencing a serious crisis of the elites, as a result of their isolation from society and its problems, which made the masses lose their confidence in the elites, especially in their pioneering role in the field of freedom, democracy and pluralism.